2011
DOI: 10.1152/ajprenal.00741.2010
|View full text |Cite
|
Sign up to set email alerts
|

Gender difference in antidiuretic response to desmopressin

Abstract: Increased age and female gender are well-known risk factors for the development of desmopressin-induced hyponatremia. However, little focus has been on exploring gender differences in the antidiuretic response to desmopressin. Based on an exploratory analysis from three clinical trials, we report a significant gender difference in the effects of desmopressin on nocturnal urine volume that could not be explained by pharmacokinetic differences. Mean desmopressin concentration profiles were tested for covariates,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
77
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 122 publications
(90 citation statements)
references
References 21 publications
11
77
0
2
Order By: Relevance
“…It was e.g. demonstrated in adults that there is a significant effect of sex on the DDAVP PD [38]. This effect is thought to be caused by a difference in V2-receptor expression [39] and should also be investigated in children.…”
Section: Discussionmentioning
confidence: 99%
“…It was e.g. demonstrated in adults that there is a significant effect of sex on the DDAVP PD [38]. This effect is thought to be caused by a difference in V2-receptor expression [39] and should also be investigated in children.…”
Section: Discussionmentioning
confidence: 99%
“…Sex diff erences in occurrence of hyponatremia caused by AD were primarily associated with hormonal activity. Th us, estrogen (but not progesterone) stimulates the secretion of AVP [34], and women may have a higher sensitivity on ADH with an increase in the expression of vasopressin renal receptors [35]. However, there are studies, whose results have not shown the infl uence of sex on the incidence of hyponatremia with the use of AD therapy [2,21].…”
Section: Discussionmentioning
confidence: 99%
“…Beneficial effects both on short-term and long-term have been confirmed [19,20]. Adverse effects are limited; however, a risk for potentially fatal hyponatriemia has to be taken in account, definitely in an older population and in women who seem to be more prone to this adverse effect [21].…”
Section: Therapeutical Implicationsmentioning
confidence: 97%